Enhanced vaccination effect against influenza by prebiotics in elderly patients receiving enteral nutrition. Issue 2 (22nd January 2015) - Akatsu, Hiroyasu; Nagafuchi, Shinya; Kurihara, Rina; Okuda, Kenji; Kanesaka, Takeshi; Ogawa, Norihiro; Kanematsu, Takayoshi; Takasugi, Satoshi; Yamaji, Taketo; Takami, Masao; Yamamoto, Takayuki; Ohara, Hirotaka; et al.
Abstract : Aim: We investigated the effect of prebiotics on the immunological response after influenza vaccination in enterally fed elderly individuals. The intervention group was given an enteral formula containing lactic acid bacteria‐fermented milk products. In addition, two different types of other prebiotics, galacto‐oligosaccharide and bifidogenic growth stimulator, were also given. The two prebiotics improved intestinal microbiota differently. In a control group, a standard formula without prebiotics was given. Methods: An enteral formula with (intervention group [F]) or without (control group [C]) prebiotics was given through percutaneous endoscopic gastrostomy to elderly participants for 10 weeks. Influenza vaccine was inoculated at week 4. Nutritional and biochemical indices, intestinal micro bacteria and immunological indices were analyzed. Results: The Bifidobacterium count in groups F and C at week 0 was 6.4 ± 1.9 and 6.6 ± 3.0 (log10 [count/g feces]), respectively. Although the count in group C decreased at week 10, the count in group F increased. The Bacteroides count in group F increased from 10.7 ± 0.9 to 11.4 ± 0.5, but decreased in group C from 11.2 ± 0.2 to 10.7 ± 0.4. Although the enhanced titers of H1N1, H3N2 and B antigens against the vaccine decreased thereafter in group C, these enhanced titers in group F could be maintained. Conclusion: Our findings suggest that prebiotics affect the intestinal microbiota and might maintain the antibody titers in elderly individuals.Geriatr Gerontol Int 2016; 16: 205–213.